Methods of preventing baby pig anemia compared - B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1969)
Anemia as it most frequently occurs in baby pigs usually is caused by an iron deficiency. Iron stored in a baby pig is extremely limited and is quickly used to produce hemoglobin to maintain oxygen-carrying capacity in the blood. Supplemental iron is needed almost immediately since the quantity of iron received from sow's milk is extremely small.; Swine Day, Manhattan, KS, September 25, 1969
Keywords: Swine day; 1969; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 151; Swine; Anemia; Iron